Analisis Penyebab Produk Defect Jenis Dust di Proses Visual Inspection Menggunakan Metode Failure Mode and Effect Analysis (FMEA) - Purwani, Ayu Putri; Safariyani, Eva; Anbiya, Muhammad Primasuri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT XYZ is a manufacturing company that produces electronics. During the production process, a significant issue has been identified - a high number of defective products due to dust contamination. This research is designed to analyze the factors contributing to these defects during the visual inspection process, using the Failure Mode and Effect Analysis (FMEA) method. This research can identify the factors causing failure, the severity level, and the probability of negative effects of the failure. Additionally, it allows us to determine the corrective actions or improvements needed to prevent or reduce the risk of product failure during the visual inspection process. The results of the research indicate that the primary cause of the NG dust-type products, based on the highest Risk Priority Number (RPN) value of 320, is operator skills. This factor is a potential cause of the NG dust-type products. Therefore, analysis and simulation of proposed improvements are being conducted, to reduce the number of NG products in the visual inspection process.